The pharmacology of the prostaglandin D2 receptor 2 (DP2) receptor antagonist, fevipiprant. (June 2021) - Brightling, Chris; Kulkarni, Swarupa; Lambrecht, Bart N.; Sandham, David; Weiss, Markus; Altman, Pablo
Abstract: Fevipiprant is an oral, non-steroidal, highly selective, reversible antagonist of the prostaglandin D2 (DP2 ) receptor. The DP2 receptor is a mediator of inflammation expressed on the membrane of key inflammatory cells, including eosinophils, Th2 cells, type 2 innate lymphoid cells, CD8 + cytotoxic T cells, basophils and monocytes, as well as airway smooth muscle and epithelial cells. The DP2 receptor pathway regulates the allergic and non-allergic asthma inflammatory cascade and is activated by the binding of prostaglandin D2 . Fevipiprant is metabolised by several uridine 5′-diphospho glucuronosyltransferase enzymes to an inactive acyl-glucuronide (AG) metabolite, the only major human metabolite. Both fevipiprant and its AG metabolite are eliminated by urinary excretion; fevipiprant is also possibly cleared by biliary excretion. These parallel elimination pathways suggested a low risk of major drug-drug interactions (DDI), pharmacogenetic or ethnic variability for fevipiprant, which was supported by DDI and clinical studies of fevipiprant. Phase II clinical trials of fevipiprant showed reduction in sputum eosinophilia, as well as improvement in lung function, symptoms and quality of life in patients with asthma. While fevipiprant reached the most advanced state of development to date of an oral DP2 receptor antagonist in a worldwide Phase III clinical trial programme, the demonstrated efficacy did not support further clinical development in asthma.